Spatial Audio - Jung-Woo Choi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This special issue compiles some of the latest state-of-the-art research works in the area of spatial audio and it serves as a good reference for both undergraduate and postgraduate students, and to researchers working in this exciting area of spatial audio.